2021
DOI: 10.3390/en14248447
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Testing Procedure of Numerical Differential Protection Relay for EHV Auto Transformer

Abstract: In power systems, the programmable numerical differential relays are widely used for the protection of generators, bus bars, transformers, shunt reactors, and transmission lines. Retrofitting of relays is the need of the hour because lack of proper testing techniques and misunderstanding of vital procedures may result in under performance of the overall protection system. Lack of relay’s proper testing provokes an unpredictability in its behavior, that may prompt tripping of a healthy power system. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…PSO algorithm has a great potential to optimize parameter settings (Behera et al, 2016). Apart from industrial processes the applications relating to power system can be found in the literature this research is focused on the power system application and optimization (Ehsan et al, 2021;Shehzad et al, 2021;Chi et al, 2021;Autonomous, 2021;Guasti Junior and Santos, 2021;Lau and Lim, 2018;Fan et al, 2019;Hu and Eberhart, 2002;Dashtdar et al, 2022;Soliman et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…PSO algorithm has a great potential to optimize parameter settings (Behera et al, 2016). Apart from industrial processes the applications relating to power system can be found in the literature this research is focused on the power system application and optimization (Ehsan et al, 2021;Shehzad et al, 2021;Chi et al, 2021;Autonomous, 2021;Guasti Junior and Santos, 2021;Lau and Lim, 2018;Fan et al, 2019;Hu and Eberhart, 2002;Dashtdar et al, 2022;Soliman et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In today's widespread population across the globe, and the fast revolution of technology from high voltage to low voltage power system networks, protection relay plays an important role in preserving the power system and eliminating abnormality within a few cycles [1], [2]. Yet, as power relay comes in different types and functions, such as current relay, and voltage relay, digital relays have developed more efficient functions in terms of current, voltage, and frequency measurement accuracy and power automation systems [3], [4]. Therefore, this work will investigate the numerical relay in terms of the internal logical microprocessor digitizing process as the bottleneck between the real and digitized spectrum to enhance the operation of power system protection.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], a setup based on the IEC61850 standard was proposed to prevent the maloperation of the differential relay in the face of harmonic currents. In addition, in [17,18], the step-by-step test of the numerical differential relay, which is used to protect a power transformer, has been described using a relay tester device.…”
Section: Introductionmentioning
confidence: 99%